2017
DOI: 10.1007/s11255-017-1698-4
|View full text |Cite
|
Sign up to set email alerts
|

Value of bioimpedance analysis estimated “dry weight” in maintenance dialysis patients: a systematic review and meta-analysis

Abstract: In ESKD patients, BIA-based interventions for correction of overhydration have little to no effect on all-cause mortality, whereas BIA improved systolic blood pressure control. Our results should be interpreted with caution as the size and power of the included studies are low. Further studies, larger or with a longer follow-up period, should be performed to better describe the effect of BIA-based strategies on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 27 publications
0
62
1
2
Order By: Relevance
“…On the other hand, in an older study, the same group had found that risk prediction for death by assessing fluid status was improved only by using BIA but not by using LUS [76]. Although the majority of the previous observational studies showed a reduction in mortality in ESRD patients, in a recent metaanalysis that included only randomized controlled trials, BIA was not associated with a significant improvement in survival, showing only a better BP control [25].…”
Section: Bioimpedancementioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, in an older study, the same group had found that risk prediction for death by assessing fluid status was improved only by using BIA but not by using LUS [76]. Although the majority of the previous observational studies showed a reduction in mortality in ESRD patients, in a recent metaanalysis that included only randomized controlled trials, BIA was not associated with a significant improvement in survival, showing only a better BP control [25].…”
Section: Bioimpedancementioning
confidence: 96%
“…However, as the meta-analysis indicated, such negative results may be explained by the overall small sample size [25]. Although there are few studies comparing other objective methods (BNP [26], Carotid artery Doppler [27]) with classical methods, further studies with larger sample sizes are needed to establish a significant outcome (Table 1) …”
Section: Dry Weightmentioning
confidence: 99%
“…Although one study showed a reduction in mortality with BIS-guided treatment [65], this did not reach significance in 2 subsequent meta-analyses. However, a reduction in pre-dialytic blood pressure was observed with the use of BIS, as well as a reduction in [39,66] FO especially in patients without residual renal function. Enthusiasm for the use of relative BV as a tool for treatment prescription has subsided, since the results of the CLIMB study, which showed that the use of a protocol based on changes in relative BV, was actually associated with an increased mortality.…”
Section: Can Technology Aid the Clinical Decision Process?mentioning
confidence: 99%
“…Evidence of the impact of BIS‐guided fluid management on survival is still lacking (Covic et al . ) and one limitation of the current adoption of this technology is the use of it in isolation rather than as a part of clinical assessment. It is important to recognise BIS is adding information to an already complex decision‐making process, rather than providing a simple target applicable to all patients (Scotland et al .…”
Section: Introductionmentioning
confidence: 99%